2013
DOI: 10.1007/s00203-013-0920-8
|View full text |Cite
|
Sign up to set email alerts
|

Genes from the exo–xis region of λ and Shiga toxin-converting bacteriophages influence lysogenization and prophage induction

Abstract: The exo–xis region, present in genomes of lambdoid bacteriophages, contains highly conserved genes of largely unknown functions. In this report, using bacteriophage λ and Shiga toxin-converting bacteriophage ϕ24Β, we demonstrate that the presence of this region on a multicopy plasmid results in impaired lysogenization of Escherichia coli and delayed, while more effective, induction of prophages following stimulation by various agents (mitomycin C, hydrogen peroxide, UV irradiation). Spontaneous induction of λ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 43 publications
3
53
0
Order By: Relevance
“…Similarly, other authors could not identify these two genes in Stx2a phages from an O104:H4 EAHEC strain of the 2011 German outbreak (Beutin et al, 2012, from an O111:H2 EAHEC strain , and two O157:H7 STEC strains (Yin et al, 2015). The exo-xis region, that was proposed to participate in the regulation of lysogenization and the promotion of phage induction, also differs from those described in 933W and Φ24 b prophages (Bloch et al, 2013;Licznerska et al, 2016). Interestingly, despite the particular characteristics of early regulatory genes in ArgO145, phage titers were similar for strains EDL933 and FB5, both in basal and induced conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, other authors could not identify these two genes in Stx2a phages from an O104:H4 EAHEC strain of the 2011 German outbreak (Beutin et al, 2012, from an O111:H2 EAHEC strain , and two O157:H7 STEC strains (Yin et al, 2015). The exo-xis region, that was proposed to participate in the regulation of lysogenization and the promotion of phage induction, also differs from those described in 933W and Φ24 b prophages (Bloch et al, 2013;Licznerska et al, 2016). Interestingly, despite the particular characteristics of early regulatory genes in ArgO145, phage titers were similar for strains EDL933 and FB5, both in basal and induced conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Monitoring of phage lytic development during one round of infection of the E. coli host cells. Lytic cycle of the tested bacteriophages was studied in one-step growth experiments, according to the procedure described by Bloch and others (Bloch et al, 2013). Host bacteria were grown in the LB medium at 30 o C to A 600 =0.2.…”
Section: Methodsmentioning
confidence: 99%
“…These data indicated that overexpression of the exo-xis region impairs the lysogenization process and contributes to a decreased transcription from the cII-stimulated promoters p I , pa Q and p E , which are responsible for promotion of the lysogenic cycle (Łoś et al, 2008a). Moreover, a few years later it was demonstrated that more efficient induction of λ and Φ24 B prophages, induced by mitomycin C and hydrogen peroxide, occurred in cultures of host cells bearing a plasmid with the exo-xis region (Bloch et al, 2013). Following prophage induction, an increase in the phage DNA amount was significantly higher in lysogenic E. coli cells containing plasmid-borne exo-xis region, while survival rate of such bacteria was lower (Bloch et al, 2013 andBloch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulatory processes are indicated as thin arrows and thin blunt-ended lines (positive regulations are represented by arrows and negative regulations are represented by blunt-ended lines). This figure is an updated version of the scheme published by Węgrzyn, Licznerska, and Węgrzyn (2012), with included data reported by Bloch et al (2013), Kwan et al (2013), and Olszewski et al (2014).…”
Section: The Level Of Complexity Of the Systemmentioning
confidence: 99%